Microalbuminuria can predict the development of acute kidney injury in intensive care unit admission - G., Bharath; Kumar, Prasanna; V., Mahendra S. (International Journal of Advances in Medicine, 2020)
Background: Microalbuminuria, defined as 30–300 mg/day of albumin excretion in urine is a common finding in ICU patients and has shown not only as a predictor of organ failure but prolonged intensive care unit (ICU) stay. Objective of the study was to determine the prediction of acute kidney injury using urine microalbuminuria and to determine the presence of urine microalbuminuria and relationship between ICU length of stay. Methods: The present study is conducted on patients admitted to Medical ICU in SDMCMSH, Dharwad from December 2016 to November 2017. 75 patients who met the inclusion and exclusion criteria were included in the study. Results: The present study included 75 patients, among which 50 were males and 25 were females. The mean age was 60.2years. AKI was developed more in non-diabetics than diabetics and non-hypertensives than hypertensives. The median urine microalbumin at admission in AKI was 80.9 and at 48 hr was130.1 predicted the AKI mean (1.79) in 59 patients with a p value of <0.001 using Mann Whitney test and P value statistically significant. Conclusions: Urine microalbuminuria at 48 hr has predicted AKI in 59 patients with median of 130.1 with statistical significance. Urine microalbuminuria of high value in AKI is directly proportional to prolonged ICU stay. At 48 hours of admission, increased levels of microalbuminuria compared at admission and 48 hour, indicates its prognostic significance among AKI and NON-AKI’s in ICU patients.